Brief Psychiatric Screening Questionnaire in Parkinson’s Disease - Will Lee; David R. Williams; Andrew Evans (Parkinson's Disease)
Background. While numerous validated questionnaires measuring psychiatric symptoms in Parkinson’s disease (PD) are available, a quick multifaceted screening tool is lacking. Objective. To generate the Brief Psychiatric Questionnaire (BPQ) that quickly screens for depression, anxiety, and apathy and to evaluate its content validity against three reference scales. Methods. Forty-seven questions were drafted and measured against the Geriatric Depression Scale (GDS), State Trait Anxiety Inventory (Form Y2) (STAI-Y2), and Apathy Evaluation Scale (AES). Data were reduced by principal component analysis and linear regression. Content validity and repeatability were assessed in a second cohort. Results. Data from ninety-five patients were used for BPQ development. Variation explained by the final linear regression models was 52% for GDS (R2 = 0.521, F(2,94) = 49.97, p<0.0001), 65% for STAI-Y2 (R2 = 0.652, F(4,94) = 42.08, p<0.0001), and 14% for AES (R2 = 0.135, F(1,94) = 14.51, p<0.0001). From the initial pool, only five questions remained for further testing. BPQ questions correctly identified 88% in the second cohort of 33 patients scoring more than five on GDS and 91% who scored in the highest decile of STAI-Y2, but only 51% who scored in the highest decile of AES. Moderate to strong correlation (r = 0.464 − 0.733, p<0.004) between predicted scores based on BPQ questions and actual scores of three validated questionnaires was demonstrated. Good repeatability of BPQ questions was demonstrated by moderate to high intraclass correlation coefficients (0.47–0.772, p<0.01). Conclusions. BPQ questions were able to accurately identify patients at risk of depression and anxiety but not apathy. It is brief and multifaceted and can act as a preconsultation tool to prompt further psychiatric assessment.